A Study of Arbuscular Mycorrhizal Association in Three Species of Asterella (Aytoniaceae, Marchantiophyta) from Western Himalayan Region, India - Pratibha Kumari; Priti Giri; Prem Lal Uniyal (Lilloa, 2025)
Most plant species including bryophytes and pteridophytes, develop mutualistic connections with arbuscular mycorrhizal (AM) fungi that facilitate greater water and nutrient uptake in plants and provide enhanced resistance against various biotic and abiotic stresses. The present study explores the diversity of AM associated with the thalloid liverwort Asterella sp. Three species of Asterella (A. khasyana, A. blumeana, and A. wallichiana) were studied to determine their association with AM fungi. The fungal association present in both types of rhizoids (smooth-walled and tuberculate) shows a higher degree of colonization in the smooth walled rhizoids as compared to the tuberculate rhizoids, validating the differential role of absorption performed by both types of rhizoids. A. khasyana and A. blumeana show the presence of both septate and aseptate fungal hyphae in their rhizoids, confirming the association of more than one fungus. Apart from rhizoids, the storage and midrib regions of the thallus show intense fungal colonization. Various AM structures, such as arbuscules and vesicles, are also observed in both rhizoids and the thallus. Spores of nine fungal species belonging to two genera, Glomus and Gigaspora were isolated from the rhizosphere soil of A. Khasyana and A. wallichiana.